Magnetic Membranes for the Remediation of Oil-Industry Effluents: Efficient Polyaromatic Hydrocarbon Removal and Marine Oil-Spill Cleanup - Costa, José Arnaldo S. [UNESP]; Oliveira, Rhayza Victoria M.; Romão, Luciane P. C. [UNESP]; Paranhos, Caio M. (American Chemical Society (ACS), 2023)
The contamination of aquatic bodies from oil or petroleum spills is increasingly common throughout the world. In this context, our very current and relevant approach was based on the preparation of magnetic mixed matrix membranes (MMMs) from the incorporation of magnetic nanomaterials to act in crude oil remediation systems. The MMMs were prepared via the casting method using magnetic nanomaterials as filler materials. They were applied to water static sorption, transport tests, permeation of polycyclic aromatic hydrocarbon (PAH), and crude oil remediation. The MMMs exhibited a homogeneous aspect with a good dispersion and excellent compatibility between the magnetic nanomaterials and the polymeric matrices as well as a good elemental distribution in the MMMs. Furthermore, it was possible to observe a decrease in the glass transition temperature (Tg) for the poly(sulfone)-based (PSf) MMMs with cobalt ferrite (CoFe2O4), and the same behavior was seen for the poly(sulfone) acrylate-based (PSf-Ac) MMM with 1.0 wt % of MCM-48-CoFe2O4-NH2 (Mobil Composition Matter of number 48). The PAH permeation tests showed that a permeation equilibrium was obtained in 24 h. The permeation, retention, and removal rates varied between: (i) 2.22-5.40%, 94.60-97.78%, and 13.91-86.53% for the PSf-based membranes and (ii) 2.23-5.44%, 94.56-97.77%, and 1.67-95.73% for the PSf-Ac-based MMMs. Finally, the results of oil remediation exhibited excellent removal values for light and heavy oil in fresh water and seawater, whose removal efficiency was between 94.08 and 99.99%. Therefore, we are optimistic about the possibility of proposing the real use of a multifunctional membrane to act in the efficient removal of organic pollutants from wastewater as well as in the magnetic removal of petroleum in aquatic bodies.
Keywords: crude oil remediation; magnetic mixed matrix membrane; polyaromatic hydrocarbon; transport properties